Comparison of Secondary School Teacher’s Professionalization and Commitment Regarding Principals’ in Secondary Schools - Ahmed, Sahira; Jamil, Mubashrah (Annals of Human and Social Sciences, 2023)
The study was aimed to compare of secondary school teacher’s professionalization and commitment regarding principals’ point of view in public and private schools in D. G. Khan (Punjab). Following were the research objectives, to determine secondary school teachers’ professionalization in terms of their professional commitment, to explore professional commitment of secondary school teachers in terms of following factors: a) Professional satisfaction, b) Professional attitude; and to analyze principal’s responses about their teacher’s professional commitment. The research background was to evaluate the level of professionalization and commitment of teachers who are preparing the next generation. Quantitative research method was used meanwhile 150 principals, 77 from public schools and 73 from private schools selected as sample from district D. G. Khan. Data was collected through questionnaire. Statistical package for social sciences (SPSS-26) was used for data analysis and relevant test were applied for hypothesis testing. Result of the study concluded that majority of the principal perceived that most important indicator “I am teacher by choice” used on teacher’s comparisons of teacher commitment and professionalization of both public and private school. Private school teachers were proud to become a teacher by their own choice as compared to public school teacher. “Teachers’ Satisfaction with their Profession” were found among male teachers then female. Gender differences still prevail in south Punjab especially in Dera Ghazi Khan.